Effects of aeration, U.V. treated seawater and antibiotics on larval growth and spatfall in Pinctada fucata (Gould) - Dharmaraj, S; Shanmugasundaram, K (Indian Journal of Fisheries, 2011)
The larvae of the Indian pearl oyster Pinctada fucata were found to have beenaffected adversely by aeration during larval phase and consequently thegrowth, and spatfall were found to be poor. The values obtained in larvalgrowth and spatfall were always less in U.V. treated seawater when comparedto unsterilised seawater. This may be due to the destruction of nannoplanktersby U.V. irradiation. Among the antibiotics tested, the performance ofkanamycin was found to be better at 50 and 100 ppm in respect of growthand spatfall.